Development of Final Consonant Writing Skill Using Multi-media of the Thai Language Strand of Prathom Suksa 1 Students in Mueang Phosri Cluster Schools under Ubon Ratchathani Primary Educational Service Area Office 4 - ทองมนต์ รัตน์วดี; เอกะกุล ธีรวุฒิ (Ubon Ratchathani Journal of Research and Evaluation, 2021)
The purposes of this research were 1) to find effectiveness of multi-media for the Thai language, 2) compare the result of the development of final consonant writing skill using multi-media of the Thai language before and after learning of the experimental group, and 3) compare the result of the development of the writing skill before and after learning of the experimental and the control groups. The samples, purposely selcted, were 13 Prathom Suksa 1 students from Ban Pho School as the experimental group, and 11 Prathom Suksa 1 students from Ban Maed Kum Lue Cha as the control group. The instruments were the multi-media, lesson plans and a test. The statistics consisted of percentage, mean, standard deviation, wilcoxon range, and the Mann-Whitney U Test. The research findings were as follows: The effectiveness of the multi-media for the Thai language strand was 83.27/81.92 which was higher than the established criteria 80/80. The development of the final consonant writing skill of the experimental group after learning was higher than before learning with statistical significance at level .05. The development of the final consonant writing skill of the experimental group was higher than the control group with statistical significance at level .05.